TASK-TECHNOLOGY FIT AND PERSON-JOB FIT: A BEAUTY CONTEST TO IMPROVE THE SUCCESS OF INFORMATION SYSTEMS - Suryani, Woro Dwi; Sumiyana, Sumiyana (Journal of Indonesian Economy and Business, 2014)
This study raises the issue that information system success could be enhanced by complementingother factors. This study investigates the success of information systems by inducing2the task-technology fit (TTF) and person-job fit (PJF) into the DeLone and McLean model. Thisstudy aims to examine, among the two induced factors, which one is able to explain andimprove the success of the information systems implementation.The results of this study indicate that the TTF explains the modelsâ goodness of fit betterthan that of the PJF when induced into the modified DeLone and McLean model. This studyimplies this in terms of both theory and practice. Theoretically, this research presents an alternativeresearch model that can be used to investigate the success of information systems byconsidering the aspect of the usersâ cognitive suitability (the cognitive fit theory). Furthermore,practically, this study suggests the importance of focusing on usersâ skills and competenciesand, subsequently, management should do so. Additionally, the TTF recommends a simpleproposition that it could be attached immediately into the individualsâ skills and competencies.However, the PJF needs to be deeply embedded in the jobâs qualifications and recruitmentpolicies.Keywords: DeLone and McLean Model, inducement, task-technology fit, person-job fit